The Impact of Cumulative Depression Along the HIV Care Continuum in Women Living With HIV During the Era of Universal Antiretroviral Treatment. (1st November 2019) - Mills, Jon C.; Pence, Brian W.; Edmonds, Andrew; Adedimeji, Adebola; Schwartz, Rebecca M.; Kassaye, Seble; Cocohoba, Jennifer; Cohen, Mardge H.; Neigh, Gretchen; Fischl, Margaret A.; Kempf, Mirjam-Colette; Adimora, Adaora A.
Abstract : Background: Data are limited on cumulative impacts of depression on engagement in care and HIV outcomes in women living with HIV (WLWH) during the era of universal antiretroviral therapy (ART). Understanding the relationship of accumulated depression with HIV disease management may help identify benefits of interventions to reduce severity and duration of depressive episodes. Setting: A cohort of WLWH (N = 1491) from the Women's Interagency HIV Study at 9 sites across the US. Methods: This longitudinal observational cohort study (2013–2017) followed WLWH for a maximum of 9 semiannual visits. Depression was quantified as a time-updated measure of percent of days depressed (PDD) created from repeated assessments using the Center for Epidemiologic Studies Depression scale. Marginal structural Poisson regression models were used to estimate the effects of PDD on the risks of missing an HIV care appointment, <95% ART adherence, and virological failure (≥200 copies/mL). Results: The risk of missing an HIV care appointment [risk ratio (RR) = 1.16, 95% confidence interval = 0.93 to 1.45; risk difference (RD) = 0.01, −0.01 to 0.03], being <95% ART adherent (RR = 1.27, 1.06–1.52; RD = 0.04, −0.01 to 0.07), and virological failure (RR = 1.09, 1.01–1.18; RD = 0.01, −0.01 to 0.03) increased monotonically with increasing PDD (comparing those with 25 to those with 0 PDD). The total effect of PDD on virological failure was fully (%100) mediated by being <95% ART adherent. Conclusions: Time spent depressed increases the risk of virological failure through ART adherence, even in the era of universal ART regimes forgiving of imperfect adherence. Abstract : Supplemental Digital Content is Available in the Text.